Approach to the Development of Human Capital - S. A. Antonov (Управление)
This paper analyzes theoretical justifications of the human capital development process and observed effects. The author looks at dependence between financing and level of human capital development, defines reproduction and implementation models, and takes an attempt to define basic elements, key questions and problems of the human capital reproduction and development models. Actualizing more in-depth study of a social capital and quality of life area, at the same time, as the main problem lying in the basis of the human capital development is determination of the balancing principles of social and economic parameters.